Emission behaviour studies on the cause of ZnO nanoparticle inclusion in neat biodiesel. Issue 16 (17th August 2020) - Rangabashiam, Devaraj; Rathinam, Sivasubramanian; Subbiah, Ganesan; j. b., Sajin; s, Suresh Babu
ABSTRACT: This work analyzes the emission characteristics of cashew nut shell biodiesel-fueled diesel engine with zinc oxide nanoparticle at various particle sizes (10 nm and 20 nm). Zinc oxide (ZnO) at a particle size of 10 nm and 20 nm were blended with cashew nut shell biodiesel using ultrasonicator, and the physicochemical properties were measured. Results revealed that cashew nut shell biodiesel promotes a lower level of hydrocarbon (HC), carbon monoxide (CO), and smoke emissions with a significant increase in carbon dioxide (CO2 ) and nitrogen oxide (NOx ) emissions. By adding 10 nm, the particle size of ZnO nanoparticle in cashew nut shell biodiesel reduces the CO, HC, smoke and NOx emission. The addition of ZnO nanoparticle at higher particle size in base fuel further reduces the CO, HC, smoke and NOx emissions.